Impact of Running Exercise Duration on Leg Muscle Strength among the people Joining Indorunners Bandung Community - Agaprita Eunike Sirait; Yuni S. Pratiwi; Ginna Megawati (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Indorunners Bandung is a community for runners that has a routine exercise schedule for running around the city of Bandung. Exercise, like running, if is conducted in an accurate duration may improve physical fitness. One of the aspects of physical fitness is leg muscles strength. Many people fail to fathom the importance of exercise duration, so, they fail to get the benefit. The aim of this study was to discover the impact of running exercise duration on leg muscles strength among the people joining Indorunners Bandung community.Methods: A comparative study was conducted to 41 people, 31 males and 10 females, of Indorunners Bandung community from September to November 2015. Each participant filled a questionnaire about his/her personal data, and then was grouped by his/her duration of exercise per week, which were 150 minutes/week, 150–299 minutes/week, and 300 minutes/week or more. The respondents were measured for their leg muscles strength. The data collected were analyzed using ANOVA test.Results: There was significant difference of lower extremities muscle strength both in men (p<0.001) and women (p=0.029). These results showed that there was a difference in leg muscles strength among the people joining Indorunners Bandung community with different exercise duration per week.Conclusions: There is a difference in leg muscles strength among the people joining Indorunners Bandung community with different exercise duration per week. [AMJ.2017;4(1):69–72]DOI: 10.15850/amj.v4n1.672